Get expert advice and insights on any topic with IDNLearn.com. Get accurate and timely answers to your queries from our extensive network of experienced professionals.
Sagot :
To determine what happens to the puppy's kinetic energy as she slows down, we'll use the kinetic energy equation:
[tex]\[ KE = \frac{1}{2} m v^2 \][/tex]
where:
- [tex]\( KE \)[/tex] is the kinetic energy,
- [tex]\( m \)[/tex] is the mass of the puppy,
- [tex]\( v \)[/tex] is the speed of the puppy.
Let's start by calculating the initial kinetic energy when the puppy's speed is 2 meters/second.
1. Initial Kinetic Energy Calculation:
[tex]\[ m = 3 \, \text{kg} \][/tex]
[tex]\[ v_{\text{initial}} = 2 \, \text{m/s} \][/tex]
[tex]\[ KE_{\text{initial}} = \frac{1}{2} \times 3 \, \text{kg} \times (2 \, \text{m/s})^2 \][/tex]
[tex]\[ KE_{\text{initial}} = \frac{1}{2} \times 3 \times 4 \][/tex]
[tex]\[ KE_{\text{initial}} = \frac{1}{2} \times 12 \][/tex]
[tex]\[ KE_{\text{initial}} = 6 \, \text{J} \][/tex]
2. Final Kinetic Energy Calculation:
Now, let's calculate the final kinetic energy when the puppy slows down to a speed of 1 meter/second.
[tex]\[ v_{\text{final}} = 1 \, \text{m/s} \][/tex]
[tex]\[ KE_{\text{final}} = \frac{1}{2} \times 3 \, \text{kg} \times (1 \, \text{m/s})^2 \][/tex]
[tex]\[ KE_{\text{final}} = \frac{1}{2} \times 3 \times 1 \][/tex]
[tex]\[ KE_{\text{final}} = \frac{1}{2} \times 3 \][/tex]
[tex]\[ KE_{\text{final}} = 1.5 \, \text{J} \][/tex]
3. Change in Kinetic Energy:
To determine what happens to the kinetic energy, we need to find the change in kinetic energy between the initial and final states.
[tex]\[ \Delta KE = KE_{\text{initial}} - KE_{\text{final}} \][/tex]
[tex]\[ \Delta KE = 6 \, \text{J} - 1.5 \, \text{J} \][/tex]
[tex]\[ \Delta KE = 4.5 \, \text{J} \][/tex]
The kinetic energy decreases; the amount of decrease is from 6 J to 1.5 J.
Therefore, the correct answer is:
A. Her kinetic energy decreases to 1.5 J.
[tex]\[ KE = \frac{1}{2} m v^2 \][/tex]
where:
- [tex]\( KE \)[/tex] is the kinetic energy,
- [tex]\( m \)[/tex] is the mass of the puppy,
- [tex]\( v \)[/tex] is the speed of the puppy.
Let's start by calculating the initial kinetic energy when the puppy's speed is 2 meters/second.
1. Initial Kinetic Energy Calculation:
[tex]\[ m = 3 \, \text{kg} \][/tex]
[tex]\[ v_{\text{initial}} = 2 \, \text{m/s} \][/tex]
[tex]\[ KE_{\text{initial}} = \frac{1}{2} \times 3 \, \text{kg} \times (2 \, \text{m/s})^2 \][/tex]
[tex]\[ KE_{\text{initial}} = \frac{1}{2} \times 3 \times 4 \][/tex]
[tex]\[ KE_{\text{initial}} = \frac{1}{2} \times 12 \][/tex]
[tex]\[ KE_{\text{initial}} = 6 \, \text{J} \][/tex]
2. Final Kinetic Energy Calculation:
Now, let's calculate the final kinetic energy when the puppy slows down to a speed of 1 meter/second.
[tex]\[ v_{\text{final}} = 1 \, \text{m/s} \][/tex]
[tex]\[ KE_{\text{final}} = \frac{1}{2} \times 3 \, \text{kg} \times (1 \, \text{m/s})^2 \][/tex]
[tex]\[ KE_{\text{final}} = \frac{1}{2} \times 3 \times 1 \][/tex]
[tex]\[ KE_{\text{final}} = \frac{1}{2} \times 3 \][/tex]
[tex]\[ KE_{\text{final}} = 1.5 \, \text{J} \][/tex]
3. Change in Kinetic Energy:
To determine what happens to the kinetic energy, we need to find the change in kinetic energy between the initial and final states.
[tex]\[ \Delta KE = KE_{\text{initial}} - KE_{\text{final}} \][/tex]
[tex]\[ \Delta KE = 6 \, \text{J} - 1.5 \, \text{J} \][/tex]
[tex]\[ \Delta KE = 4.5 \, \text{J} \][/tex]
The kinetic energy decreases; the amount of decrease is from 6 J to 1.5 J.
Therefore, the correct answer is:
A. Her kinetic energy decreases to 1.5 J.
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com is dedicated to providing accurate answers. Thank you for visiting, and see you next time for more solutions.